Autophagy and Breast Cancer: Connected in Growth, Progression, and Therapy - Qitong Wu; Dipali Sharma (Cells, 2023)
Despite an increase in the incidence of breast cancer worldwide, overall prognosis has been consistently improving owing to the development of multiple targeted therapies and novel combination regimens including endocrine therapies, aromatase inhibitors, Her2-targeted therapies, and cdk4/6 inhibitors. Immunotherapy is also being actively examined for some breast cancer subtypes. This overall positive outlook is marred by the development of resistance or reduced efficacy of the drug combinations, but the underlying mechanisms are somewhat unclear. It is interesting to note that cancer cells quickly adapt and evade most therapies by activating autophagy, a catabolic process designed to recycle damaged cellular components and provide energy. In this review, we discuss the role of autophagy and autophagy-associated proteins in breast cancer growth, drug sensitivity, tumor dormancy, stemness, and recurrence. We further explore how autophagy intersects and reduces the efficacy of endocrine therapies, targeted therapies, radiotherapy, chemotherapies as well as immunotherapy via modulating various intermediate proteins, miRs, and lncRNAs. Lastly, the potential application of autophagy inhibitors and bioactive molecules to improve the anticancer effects of drugs by circumventing the cytoprotective autophagy is discussed.